PENGARUH CURRENT RATIO DAN RETURN ON EQUITY RASIO TERHADAP KEBIJAKAN DIVIDEN (STUDI PADA PERUSAHAAN SUB SEKTOR PERKEBUNAN YANG TERDAFTAR DI BEI) - Rustam Effendi; Herlan Junaidi (JURNAL KOMPETITIF, 2022)
This study aims to determine, analyze and prove the effect of Current Ratio and Return On Equity on Dividend Policy in plantation sub-sector companies listed on the Indonesia Stock Exchange (IDX). The population in this study was 16 plantation sub-sector companies listed on the IDX for the period 2010 - 2019. However, only 3 companies were used as samples using purposive sampling, because they met the criteria: consistently listed on the IDX and distributed dividends to shareholders. from 2010 – 2019. Based on the data that has been processed, a multiple linear regression equation is obtained: = 0.364 + 0.349X1 - 0.184X2 + e, where the constant value of 0.364 states that if there is no influence from Current Ratio and Return On Equity, then Dividend Policy score is 0.364. The regression coefficient of the Current Ratio is positive 0.349, meaning that every 1% increase in the Current Ratio will increase the Dividend Policy by 0.349 or 34.9%. The regression coefficient of Return On Equity -0.184 is negative, meaning that every 1% increase in Return On Equity will cause a decrease in Dividend Policy -0.184 or 18.4%. The value of the coefficient of determination (R2) = 0.345% indicates that the contribution of the influence of Current Ratio and Return On Equity together to Dividend Policy is 0.345 or 34.5%, the remaining 65.5% is influenced by other factors not examined. The results of hypothesis testing prove, Current Ratio and Return On Equity together have a positive and significant influence on Dividend Policy as evidenced by the value of sig F = 0.002 < 0.05. Partially, the effect of Current Ratio on Dividend Policy is significant and has a positive sign on Dividend Policy as evidenced by the value of sig t = 0.031 < 0.05. Likewise, Return on Equity has a significant but negative effect on Dividend Policy which can be proven by the value of sig t 0.002 < 0.05.Keywords: Divided Policy, CurrentRasio and ReturnOn EquityRatio